2013
DOI: 10.4103/0253-7613.121378
|View full text |Cite
|
Sign up to set email alerts
|

A comparative study to evaluate efficacy, safety and cost-effectiveness between Whitfield′s ointment + oral fluconazole versus topical 1% butenafine in tinea infections of skin

Abstract: Aims and Objectives:The aim of this study is to compare the efficacy, safety and cost-effectiveness of topical Whitfield's ointment plus oral fluconazole with topical 1% butenafine in tinea infections of the skin.Materials and Methods:Patients were randomly allocated to the two treatment groups and advised to apply either agent topically twice-a-day for 4 weeks on the lesions and fluconazole (150 mg) was administered once a week for 4 weeks in the study group applying Whitfield's ointment. Patients were follow… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 10 publications
0
6
0
1
Order By: Relevance
“…[ 83 84 ] Topical keratolytics, such as Whitfield's ointment (3% salicylic acid with 6% benzoic acid), can be used in the treatment of glabrous tinea, but not on the flexures or face or where the lesions are inflamed. [ 85 86 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 83 84 ] Topical keratolytics, such as Whitfield's ointment (3% salicylic acid with 6% benzoic acid), can be used in the treatment of glabrous tinea, but not on the flexures or face or where the lesions are inflamed. [ 85 86 ]…”
Section: Discussionmentioning
confidence: 99%
“…Very low‐quality RCT evidence also found no difference between topical sertaconazole and topical terbinafine and that topical terbinafine and topical luliconazole could not be differentiated . Similarly, low‐quality RCT evidence from India found that daily oral terbinafine or weekly fluconazole achieved similar clinical cures and topical butenafine was no better than weekly fluconazole combined with topical Whitfield's ointment (3% salicylic acid and 6% benzoic acid) at 4 weeks . Low‐quality evidence from a prospective cohort of Australian Aboriginal people with tinea corporis and tinea unguium found daily oral terbinafine cured 32% .…”
Section: Resultsmentioning
confidence: 99%
“…In another study, Global Evaluation Response revealed that skin lesions were completely cleared with Whitfield’s ointment + oral fluconazole and butenafine cream in 98% patients with tinea. However, Whitfield’s ointment caused burning and redness, oral fluconazole caused gastritis, while no adverse events were reported with topical butenafine [ 26 ]. Terbinafine and sertaconazole resulted in complete cure in 100% subjects with Tinea cruris and Tinea corporis at the end of 3 weeks of treatment [ 27 ].…”
Section: Discussionmentioning
confidence: 99%